2012
DOI: 10.1371/journal.pone.0052439
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Wheat Aquaporin Gene, TaAQP7, Enhances Drought Tolerance in Transgenic Tobacco

Abstract: Aquaporin (AQP) proteins have been shown to transport water and other small molecules through biological membranes, which is crucial for plants to combat stress caused by drought. However, the precise role of AQPs in drought stress response is not completely understood in plants. In this study, a PIP2 subgroup gene AQP, designated as TaAQP7, was cloned and characterized from wheat. Expression of TaAQP7-GFP fusion protein revealed its localization in the plasma membrane. TaAQP7 exhibited high water channel acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(128 citation statements)
references
References 80 publications
(111 reference statements)
11
114
0
3
Order By: Relevance
“…Therefore, EsMcsu1overexpression increased the ability of transgenic alfalfa plants to eliminate cellular ROS, indicating that the transgenic lines experienced less oxidative damage than the WT plants. IL, which is an index of physical damage to cell membranes (Zhou et al, 2012), was significantly lower in the leaves of TG2 and TG7 than in those of the WT plants, while no difference was observed before drought treatment (Figure 7a). In addition, MDA, which is a key indicator of ROS-mediated damage to plant cells (Moore and Roberts, 1998), exhibited a similar tendency to IL (Figure 7b).…”
Section: Esmcsu1 Overexpression Decreased Ros Il and Mda Levels Undmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, EsMcsu1overexpression increased the ability of transgenic alfalfa plants to eliminate cellular ROS, indicating that the transgenic lines experienced less oxidative damage than the WT plants. IL, which is an index of physical damage to cell membranes (Zhou et al, 2012), was significantly lower in the leaves of TG2 and TG7 than in those of the WT plants, while no difference was observed before drought treatment (Figure 7a). In addition, MDA, which is a key indicator of ROS-mediated damage to plant cells (Moore and Roberts, 1998), exhibited a similar tendency to IL (Figure 7b).…”
Section: Esmcsu1 Overexpression Decreased Ros Il and Mda Levels Undmentioning
confidence: 95%
“…Leaf water loss and water potential was measured as described by Li et al (2013). Levels of ion leakage (IL) and malondialdehyde (MDA) were detected according to the method described by Zhou et al (2012). In vivo localization and quantification of reactive oxygen species (ROS), including H 2 O 2 and O 2 − , was determined according to the methods reported by Yadav et al (2012).…”
Section: Analysis Of Biochemical and Physiological Parametersmentioning
confidence: 99%
“…It also presents the subsequent phenotypic characterization of this transgenic plant under conditions of salt and drought stress. While transgenic methods used to explore the role of plant AQPs have been reported previously (54)(55)(56), this is the first report describing the in planta heterologous expression of an aquaglyceroporin derived from a filamentous fungus. Recently, a viral aquaglyceroporin of Chlorovirus (encoded by aqpv1) has been expressed in tobacco (57).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, recent studies conducted on important monocot species have reported that the heterologous overexpression of AQP genes in transgenic plants imparts improved tolerance to cold, salt and drought stress. TaAQP8 overexpression in transgenic tobacco improved salt stress tolerance whereas ectopic expression of TaAQP7 improved the drought tolerance in tobacco plants indicating specific roles and functions of each AQP isoform in the overall management of water balance in plant cells (Zhou et al 2012). Similarly, constitutive overexpression of OsPIP1;1 improved salt tolerance in transgenic rice (Liu et al 2012) and constitutive and stress-inducible overexpression of a native plasma membrane AQP in banana improved drought, salt and cold tolerance in transgenic banana plants (Sreedharan et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%